Prenatal and postnatal methamphetamine exposure alters prefrontal cortical gene expression and behavior in mice - Adeniyi, Philip A.; Adeyelu, Tolulope T.; Shrestha, Amita; Liu, Chin-Chi; Lee, Charles C. (Frontiers in Behavioral Neuroscience, 2024)
Methamphetamine is a highly abused psychostimulant that substantially impacts public health. Prenatal and postnatal methamphetamine exposure alters gene expression, brain development, and behavior in the offspring, although the underlying mechanisms are not fully defined. To assess these adverse outcomes in the offspring, we employed a mouse model of prenatal and postnatal methamphetamine exposure. Juvenile offspring were behaviorally assessed on the open field, novel object recognition, Y-maze, and forced swim tests. In addition, RNA sequencing was used to explore potential alterations in prefrontal cortical gene expression. We found that methamphetamine-exposed mice exhibited decreased locomotor activity and impaired cognitive performance. In addition, differential expression of genes involved in neurotransmission, synaptic plasticity, and neuroinflammation were found with notable changes in dopaminergic signaling pathways. These data suggest potential neural and molecular mechanisms underlying methamphetamine-exposed behavioral changes. The altered expression of genes involved in dopaminergic signaling and synaptic plasticity highlights potential targets for therapeutic interventions for substance abuse disorders and related psychiatric complications.